Educational implications of a witch character - an extraordinary woman in the context of emancipatory pedagogy - Izabela Symonowicz-Jabłońska (Maria Curie-Skłodowska University, Lublin, Poland, 2020)
Contemplations on a woman-witch inscribed in the foundations of emancipatory pedagogy is to show modification of her current image, open up a new research opportunity that allows for a broader view of the witch as an interpreter of culture that does not fit into the main centralist trend of thinking about the world. So does the woman witch In basic mental - stereotypical human constructions seen as a destructive and malicious figure, always represent the opposite of all positive values, or can she be perceived as a positive character ? Or maybe [does she] "work in two ways: while being a myth she is both true and illusion" (Rella 2003, p. 295)? Does the image of a witch change because of adolescence? The article presents the results of the research carried out among the youth of the secondary school in Toruń. Thanks to the used focus method a catalogue of features defining the witch was created. The study involved 26 people (13 from the humanities class and 13 from the mathematics and IT class) and aimed at identifying differences in terms of verbalized values between the two groups.